MHS status and salivary cortisol concentration in individually housed pigs - Nataša SIARD; Ivan ŠTUHEC (Acta Agriculturae Slovenica)
Salivary cortisol was evaluated as stress measure in pigs of two malignant hyperthermia (MH) genotypes (NN and Nn), housed individually in metabolic cages and in comfortable large pens with straw. Three replicates were done, each including 8 German Landrace barrows, four (2 NN, 2 Nn) housed in pens and four (2 NN, 2 Nn) in metabolic cages. Altogether there were 24 animals included in the experiment. Saliva samples of all animals were collected simultaneously every 15 minutes between 8.00 and 11.00 a.m. on days 8, 22 and 36 of the experiment. Pigs in more stressful conditions (metabolic cages) had higher salivary cortisol values than pigs in pens, indicating that salivary cortisol might be a suitable indicator of stress in pigs. Higher salivary cortisol values in NN- in comparison to Nn- pigs indicated stronger response to stressful conditions in NN-genotype.